Skilled in Creating Power Products for Electronic Instruments Size E Guitar String (Star Missiles) Through Project Based Learning Models - Murdhiastuti, Henny (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2022)
This research was conducted in mathematics and sciences class XII-2 high school 1 Sigaluh, on electromagnetic induction material. The data of this research are data improving science process skills and scientific attitudes. The research instruments are in the form of observation sheets for project implementation assessments and questionnaires. The results of the questionnaire show that 63% of respondents use electricity-saving lamps, 31% have not used electricity-saving lamps, and 6% choose to be absent. The results of observation on the star missile PjBL showed an average of 81 categories of the high predicate. The results of the science teacher's response questionnaire obtained a score with the predicate category that strongly agrees with the star missile project-based learning. While the results of the cognitive assessment of the Star Missile PjBL have an average of 85, project appraisal with an average of 83.8 for star missile product appraisal has an average score of 85.8. Based on the results, it can be concluded that the application of the star missile project-based learning model can improve science process skills and scientific attitudes and is expected to can provide input for Physics teachers in implementing the star missile project-based learning model on KD 4.5.